Steppes and the silk route - C. Edmund Bosworth (The UNESCO Courier, 2023)
Samarkand, Bukhara, Herat... cities of dreams. Genghis Khan, Tamerlane, Akbar... characters who marked history. Avicenna, Khayyam, Ulugh Beg... thinkers who transformed worldviews. These names were inscribed down through the ages on a territory that corresponds not to a specific region of the ancient world but to a permanent crossroads of exchanges between peoples: Central Asia. Since antiquity, Scythians, Hsiung-nu and Khitai roamed this area, from the Caspian Sea to the Chinese border, setting the foundations for the great civilizations of Asia and Europe.